(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Considerazioni introduttive sul fondamentalismo odierno: alcune differenze rispetto ai movimenti omologhi dei decenni precedenti - 2. L’influenza del fondamentalismo sulla demografia religiosa e sul contenzioso giurisdizionale negli Stati Uniti d’America - 3. Il fondamentalismo americano protestante e le omologhe istanze etiche e giuridiche di gruppi religiosi contemporanei - 4. La Chiesa di Gesù Cristo dei Santi degli Ultimi Giorni: le origini di una protesta contro la teologia ottocentesca - 5. L’escatologia teocratica dei Testimoni di Geova e le conseguenze ordinamentali - 6. Possibili conclusioni: il ruolo del fondamentalismo cristiano nella conformazione attuale delle istituzioni statunitensi. The origins of the Christian fundamentalism: comparative approaches and research perspectives ABSTRACT: The aim of this essay is to demonstrate the Christian roots of the public discourse concerning fundamentalism, its disciplines, groups and legal consequences. This issue implies to go back to the first Christian fundamentalist experiences born and raised during last two centuries in America (with a peculiar focus on the United States). By reconsidering a wide historical period and a not simple variety of local religious communities, it will be possible to underline a substantial and concurrent beginning for similar movements in the progressive development of Jehovah’s Witnesses, new wave Lutheran and Baptist Churches, Church of Latter Day Saints: some of the same faiths and cults still effecting the American recent ecclesiastical controversies.